Genotypic Responses of Patchouli (Pogostemon cablin Benth) to Water Stress: Implications for Drought-Resistant Cultivation - Sri Nurmayanti; Muhammad Tahir; Dimas Prakoswo Widiyani; Dimas Prayoga (Jurnal Riset Perkebunan, 2025)
Patchouli is one of the C3 plants that can grow without full sunlight. Photosynthesis in C3 plants is greatly influenced by CO2 content. Unpredictable climate fluctuations can affect the productivity of this plant. Continuous rain or long droughts can affect the photosynthesis process of patchouli plants.  This study aims to evaluate the effect of water stress on the morphological and physiological characteristics of patchouli plants (Pogostemon cablin Benth). The study used a Factorial Randomized Block Design (RBD) consisting of two factors. The first factor was four genotypes of mutated patchouli: Genotypes 7, 8, 9, and 10 (as a control). The second factor was different field capacity treatments (60%, 80%, 100%, and 120%).  Observation parameters include physiological parameters, namely the number of leaves, and morphological parameters, namely main stem diameter and number of branches.  The results showed that water stress significantly affected the number of leaves, main stem diameter, and branches.  Genotype 7 showed the best growth in the parameters of main stem diameter and number of branches. Genotype 7 showed a 25% larger main stem diameter and 10% more branches at 100% field capacity than other genotypes.